2007
DOI: 10.1007/s10103-007-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of laser irradiance threshold in the induction of alkaline phosphatase in human osteoblast cultures

Abstract: Induction of matrix synthesis by low-level laser has been demonstrated extensively. However, the question of dose- or power intensity-dependency is under-investigated. To address this issue we chose human osteoblast cell cultures and measured their alkaline phosphatase (ALP) activity after laser irradiation. The cell cultures were irradiated periodically by 690 nm radiation via optical transmission fiber-based laser needles, reaching into the culture dishes. The osteoblasts showed no induction of ALP activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
10
1
1
Order By: Relevance
“…Additionally, some authors have demonstrated that different results can be obtained with the use of different power densities, which could optimize the PBM effects on the target tissue [35,36]. As this study was limited to the investigation of the effects of different fluences, tissue response under different power densities remains to be provided.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, some authors have demonstrated that different results can be obtained with the use of different power densities, which could optimize the PBM effects on the target tissue [35,36]. As this study was limited to the investigation of the effects of different fluences, tissue response under different power densities remains to be provided.…”
Section: Discussionmentioning
confidence: 90%
“…18 It was found that invitro studies of human osteoblast cells metabolism could be increased by a factor of 9.1 by laserneedle irradiation. A shift of the osteoblast-osteoclast-activity equilibrium to the bone regeneration side can be induced and maintained by the laserneedle therapy.…”
Section: New Therapeutic Possibilities Of Laserneedle Stimulationmentioning
confidence: 99%
“…22 The 102 mW/cm 2 irradiance promoted a 43% increase in ALP production, and the irradiance of 204 mW/cm 2 increased the production of ALP eightfold. 22 These results differ from ours, in which there was no increase in ALP activity with laser. 22 The study by Hirata et al is in accordance with our research.…”
mentioning
confidence: 98%
“…21 Many studies showed an increase in ALP activity after laser irradiation. [22][23][24] Haxsen et al performed a study in which osteoblasts were irradiated with a red laser 690 nm, 51, 102, or 204 mW/cm 2 , every 4 h for 24 h in total. 22 The 102 mW/cm 2 irradiance promoted a 43% increase in ALP production, and the irradiance of 204 mW/cm 2 increased the production of ALP eightfold.…”
mentioning
confidence: 99%
See 1 more Smart Citation